2006
DOI: 10.1037/0278-6133.25.5.635
|View full text |Cite
|
Sign up to set email alerts
|

The toll of ethnic discrimination on sleep architecture and fatigue.

Abstract: Most work on ethnicity tends to focus on daytime health rather than how aspects of ethnicity affect nighttime functioning. The current study examined how discrimination and ethnic identity relate to sleep architecture and fatigue in 37 African Americans and 56 Caucasian Americans. The authors conducted sleep monitoring with standard polysomnography. African Americans had less slow-wave sleep and reported more physical fatigue than did Caucasian Americans (ps < .05). The authors conducted path analyses to exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
134
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(148 citation statements)
references
References 46 publications
10
134
4
Order By: Relevance
“…These substantial population-level reductions in racial/ethnic disparities occurred despite the fact that only 15-20% of Black and Latino children reported discrimination; the effects of discrimination on this subset may be so profound that they substantially affect population-level racial/ethnic differences. These results extend prior analyses of the statistical contribution of perceived discrimination to health disparities [25][26][27][28][29] by isolating, for Black and Latino youth separately, the distinct effects of perceived discrimination on health-related problem behaviors. In the case of Latinos, these results suggest that discrimination can have an insidious impact, even when a traditionally disadvantaged group appears to have better sociodemographically-adjusted health outcomes than Whites.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…These substantial population-level reductions in racial/ethnic disparities occurred despite the fact that only 15-20% of Black and Latino children reported discrimination; the effects of discrimination on this subset may be so profound that they substantially affect population-level racial/ethnic differences. These results extend prior analyses of the statistical contribution of perceived discrimination to health disparities [25][26][27][28][29] by isolating, for Black and Latino youth separately, the distinct effects of perceived discrimination on health-related problem behaviors. In the case of Latinos, these results suggest that discrimination can have an insidious impact, even when a traditionally disadvantaged group appears to have better sociodemographically-adjusted health outcomes than Whites.…”
Section: Discussionsupporting
confidence: 78%
“…[25][26][27][28][29] These studies have demonstrated that significant associations between race/ ethnicity and health outcomes decrease or become non-significant when discrimination is controlled, suggesting that discrimination influences inequities. For example, one study found that, after controlling for everyday perceived discrimination, Black (versus White) differences in self-reported health decreased even after adjusting for socio-economic status.…”
Section: Introductionmentioning
confidence: 99%
“…Although Blacks reported more ongoing problems and less physical activity than Whites/Asians, these factors did not account for obtained differences. It is possible that cultural norms or other psychosocial variables that were not assessed, such as social support or discrimination, are more influential in Blacks' sleep (43). Physiological pathways, such as autonomic functioning, also may be relevant mechanisms for future study (44).…”
Section: Discussionmentioning
confidence: 99%
“…Discrimination can be conceptualized as impacting well-being either as a result of individual-level actions such as biased personnel decisions (Essed, 1991;Landrine and Klonoff, 1996), or ecosocial/systemic conditions such as segregation and glass ceilings (Krieger, 1999). Studies have shown that individuals subjected to discrimination develop psychological, behavioral, and physical maladies such as smoking (Landrine and Klonoff, 1996), somatization and anxiety (Klonoff et al, 1999), general mental health problems (Schneider et al, 2000;Sheridan, 2006), cardiovascular reactivity (Guyll et al, 2001), and sleep problems (Thomas et al, 2006).…”
mentioning
confidence: 99%